Legal consciousness as a prerequisite for person’s lawful behavior: retrospective view, modern interpretation - А. М. Shulha (Law and Safety)
The basics for legal consciousness as a prerequisite for lawful behavior of a person have been investigated. It has been noted that in today’s conditions the term “legal consciousness” is understood broadly, it covers, which is paradoxical or insufficiently correct from a critical point of view, both conscious and unconscious in the legal sphere of the inner world of man, that is, there is a need to distinguish between the concepts of “legal consciousness” and “legal subconsciousness”.